Disasters at sea - Donkin, Andrew (Dorling Kindersley London, 2001)
Describes shipwrecks that have occurred due to poor weather conditions or human error, highlighting the collison of two passenger ships in 1854 in thick fog and a torpedo attack on the Lusitania in 1915